2006
DOI: 10.1007/s10452-006-9029-3
|View full text |Cite
|
Sign up to set email alerts
|

Is spread of the neophyte Spartina anglica recently enhanced by increasing temperatures?

Abstract: The introduced cordgrass Spartina anglica, a fertile hybrid of S. maritima and S. alterniflora, grows as a pioneer plant in the upper intertidal zone and has invaded most sheltered shorelines of the Wadden Sea. After its introduction in 1927 S. anglica has spread vigorously along the mainland shore and on some of the more southern islands. In contrast, it has later established on Sylt and spread at a lower pace. On the island of Sylt it occurs near at its northern limit in Europe. Due to rising sea level and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 30 publications
2
46
0
Order By: Relevance
“…2). This was already recorded by Loebl et al (2006) who propose that increasing summer temperature since the 1990s has facilitated the spread of S. anglica. We also found a single pioneer plant at Kersten Rimling (Fig.…”
Section: Introduced Non-nativesmentioning
confidence: 62%
See 1 more Smart Citation
“…2). This was already recorded by Loebl et al (2006) who propose that increasing summer temperature since the 1990s has facilitated the spread of S. anglica. We also found a single pioneer plant at Kersten Rimling (Fig.…”
Section: Introduced Non-nativesmentioning
confidence: 62%
“…Most changes in the Wadden Sea have been attributed to eutrophication (e.g. van Beusekom 2005), to the loss of apex predators (Lotze 2005), fisheries (Piersma et al 2001), artificial shores (Reise 2005), alien invaders (Buschbaum et al 2012) and to climate change (Beukema and Dekker 2005;Diederich et al 2005;Loebl et al 2006;Nehls et al 2006, Witte et al 2010. Here, we add a long-term study on sandflat benthos to further unravel small-scale responses to large-scale causes in a coastal ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Much work has been undertaken on the changes of invertebrate macrobenthic assemblages associated with Spartina saltmarshes in North America (Levin and Talley 2000;Neira et al 2005;Brusati and Grosholz 2006), while there is only limited information from northern Europe (Vinther et al 2001;Gribsholt and Kristensen 2003). The Wadden Sea is treasured by its special native biodiversity and is a stepping stone for a variety of migratory waterbirds (Vinther et al 2001;Loebl et al 2006). S. anglica was introduced in the Danish Wadden Sea around 1,940 where no native Spartina species were present (Nehring and Hesse 2008).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…The expansion of S. anglica may even be accelerated in the future due to global warming (Gray and Mogg 2001;Loebl et al 2006). Danish Wadden Sea is a bird-protection area, and macroinfauna serve as important food for a variety of wading birds (Beukema et al 1993;Zwarts and Wanink 1993; Munch-Petersen and .…”
mentioning
confidence: 99%
“…The invasive saltmarsh plant Spartina spp. is currently restricted to small but dense patches in several Tasmanian and Victorian estuaries (Adam 2009;Williamson 1996), and higher temperatures may promote its further proliferation (Boon et al 2011), as has been observed in the Netherlands (Loebl et al 2006). Sea-level rise presents an opportunity and threat to coastal saltmarsh, depending on rates of sediment supply, local topographic conditions and barriers to transgression.…”
Section: Summary Of Climate Change Vulnerabilitymentioning
confidence: 99%